Demand analysis of public sports service for older adults using Kano model - Yang, Xin; Leng, Zimiao; Ma, Changning; Yang, Guanghui (Frontiers in Public Health, 2025)
AimChina is one of the countries with a relatively high degree of population aging in the world. Compared with other countries, China has the largest number of older adults and the fastest aging speed. In the increasingly serious situation of population aging, it has become the common desire of the whole society to actively develop sports for older adults and improve the health and quality of life of older adults. By identifying the needs of public sports services for older adults, this study ensures the sustainable improvement and meeting the needs of sports services for older adults in the future. The findings aim to improve the quality of life of older adults, enhance their physical and mental health.MethodsParticipants were from Haigang District, Changli County, and Funing District of Qinhuangdao City, Hebei Province, China. A total of 436 older adults who met the survey requirements were included. The socio-demographic characteristics questionnaire was used to investigate and analyze the needs of the participants for public sports services.ResultsOf the 23 quality attributes evaluated by participants, nine were “must quality,” two were “one-dimensional quality,” three were “attractive quality,” and nine were “indifferent quality.” The better values (satisfaction) ranged from 32.80 to 58.49%, and the worse values (dissatisfaction) ranged from 28.21 to 77.98%. In addition, the average ID of 23 service quality items was 2.25, and 12 attributes were above the average, which were high value-added attributes.ConclusionBased on Kano model, it is found that older adults have a positive attitude toward physical activities, and the demand for different dimensions of public sports services is different. This study provides a theoretical basis for the decision makers of public sports services for older adults to formulate corresponding policies, and provides a scientific basis for sports instructors to optimize the content of public sports services and meet the personalized and characteristic needs of public sports services for older adults which contributes to healthy aging.